Preparation of La2(WO4)3/CuWO4 composite nanomaterials with enhanced sonodynamic anti-glioma activity - Liu, Fang-Yu; Wang, Xin; Liu, Ye-Fu (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionSonodynamic therapy (SDT) is an innovative way to treat tumors by activating sonosensitizers via ultrasound (US). The development of sonosensitizers with high sonodynamic activity is the key to promote the clinical application of SDT.MethodsIn this study, a novel sonosensitizer, La2(WO4)3/CuWO4 composite LC-10, was prepared by two-step hydrothermal method and characterized. In addition, the sonodynamic antitumor activity of La2(WO4)3/CuWO4 composite LC-10 was investigated using u251 glioma cells as a model.Results and DiscussionThe results showed that compared with La2(WO4)3 and CuWO4, La2(WO4)3/CuWO4 composite had better sonodynamic antitumor activity, and LC-10 had good biosafety at concentrations below 50 μg/mL. After La2(WO4)3 and CuWO4 formed La2(WO4)3/CuWO4 composite, the recombination of electron-hole (e−–h+) pairs were effectively inhibited, and more strongly oxidizing ROS was produced, inducing apoptosis of u251 glioma cells. In which, singlet oxygen (1O2) and hydroxyl radical (·OH), especially the production of ⋅OH, played an important role in the La2(WO4)3/CuWO4 composite mediated SDT antitumor process. The results of this study would offer a foundation for the design of CuWO4 base nano-sonosensitizers and its further clinical application in SDT antitumor. In addition, it also provided a new strategy for the design and development of novel nano-sonosensitizers with excellent sonodynamic activity.